(3GdLGeY GdUZjQ ef MOjK GdHTjQ GdfPjQs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj HYK Ydi QCS cd eGFI SfI ef jLOO dgPg GdCeI CeQ OjfgG gPG cJGH ChOYJ ajg ef Gdcde GdfHhjI (B( (3cPG (B) (3CdhaG hQJHJg Ydi MQha GdeYLe hSejJg GdLGeY GdUZjQ ef MOjK GdHTjQ GdfPjQ dCfg ebJVH ef GdcJGH GdcHjQ GdPj SejJg LeY GdLhGeY s
(3BNQgG (B:s
(3Gdjhe GdehYhO jhe GdbjGeI hGdjhe GdeTghO jhe YQaI hGdTGgO jhe GdLeYI heG WdYJ GdTeS hdG ZQHJ Ydi jhe CaVd efg ajg SGYI dG jhGabgG YHO eSde jOYh Gddg HNjQ EdG GSJLGH Gddg dg hdG jSJYjP ef TQ EdG CYGPg Gddg efg (B((3J gb(B) (3Yf CHj gQjQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 301s
(3eYLe GdeDdajf (B2 / 82s
(3cTa GdXfhf (B1 / 560s
(3TPQGJ GdPgH (B8 / 51s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs